Development and Validation of RP-HPLC Method for Simultaneous Qualitative and Quantitative Estimation of Curcumin and Quercetin in Bulk Mixture - Patil, Nayana; Mahajan, Hitendra (Indian Journal of Pharmaceutical Education and Research, 2022)
Objectives: To design a definite, new and explicit reverse phase high performance liquid chromatographic (RP-HPLC) method for simultaneous estimation of quantitative and qualitative curcumin and quercetin in bulk mixture. As per guidelines of International conference on harmonization (ICH) method was validated. Materials and Methods: In this study, reverse phase analysis was used to do the analysis Younglin- ACME 9000, C18 (250 x 4.6mm i.d) solvent system methanol and 0.05% orthophosphoric acid as mobile phase in proportion of 80:20 v/v was used. The flow rate at constant rate 0.7ml/min. The absorbance of the eluted sample was analyzed by use of UV Visible detector at 254 nm. Results: The proposed improved methodology takes 5.25 min to elute curcumin and 8.78 min to elute quercetin. The system suitability parameters were studied for the developed method and were found to be within the acceptable limits. The LOQ and LOD of curcumin was reported to be 0.041 and 0.081g/ml, respectively, while quercetins were 0.0048 and 0.039g/ml. Conclusion: The designed methodology validated as per the ICH guidelines for its linearity, precision, specificity, sensitivity, accuracy, raggedness, robustness, LOD, and LOQ. The results of the preceding observations show that the procedure is effective in both qualitative and quantitative analyses of the markers in the mixture.
Keywords: RP-HPLC; Curcumin; Quercetin; Validation; Qualitative; Quantitative